2019
DOI: 10.26803/ijhss.11.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Oral Communication Proficiency in English of the Grade 5 Pupils

Abstract: This study aimed to identify the oral communication proficiency in English of the Grade 5 pupils in Bontoc Central School. Specifically, it highlighted fluency, accuracy, and nonverbal cues as they are the most commonly observed features in the oral language. Two speaking tasks were administered to the Grade 5 pupils, and two raters evaluated their performances. The result showed that the pupils' overall level of the oral communication proficiency in English is early intermediate or Grade 2 level according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…It has the highest correlation coefficient among the other dimensions, meaning there is a substantial relationship between academic self-concept and English oral proficiency. It is because curriculum and teaching strategies are significant factors in students' oral proficiency (Pangket, 2019). It can be gleaned from this finding that the respondents' experience in the classroom has affected their level of oral proficiency since it has consequently improved or downgraded their academic self-concept.…”
Section: Discussionmentioning
confidence: 94%
“…It has the highest correlation coefficient among the other dimensions, meaning there is a substantial relationship between academic self-concept and English oral proficiency. It is because curriculum and teaching strategies are significant factors in students' oral proficiency (Pangket, 2019). It can be gleaned from this finding that the respondents' experience in the classroom has affected their level of oral proficiency since it has consequently improved or downgraded their academic self-concept.…”
Section: Discussionmentioning
confidence: 94%
“…These definitions of oral fluency suggest that a fluent English speaker must avoid excessive stops and maintain a dialogue at a standard speech rate and length while exchanging opinions and beliefs. In this respect, Albino (2017) and Pangket (2019) contend that mastering speaking fluency supports students in improving their abilities to elaborate a better discourse that assists them in interacting with their classmates without anxiety. Houn and Em (2022) and Ho (2018) agree that accurate speech production encourages clear oral interaction among speakers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Effective communication across a broad range of contexts is a benchmark for students to ensure their success and growth in any industry. However, many studies have stressed that students are still struggling to effectively express their thoughts, let alone communicate in English [1,2,3]. In addition, a recent study by Al Riyami [4] suggested that effective communication in English is still a challenge for most graduates, impeding their employability and career advancements.…”
Section: Introductionmentioning
confidence: 99%
“…Al Riyami [4] listed English language problems that cause ineffective communication, which include low proficiency, lack of vocabulary, persuasive skills, and inappropriate use of language. In addition, Pangket [3] argued that English language problems such as complex structure, lack of vocabulary, and low motivation impede students' development of communication competence. Moreover, Atashian [9] found that students' first-language interference in learning English as a second language negatively impacts their ability to communicate in English.…”
Section: Introductionmentioning
confidence: 99%